2019
DOI: 10.1002/evan.21768
|View full text |Cite
|
Sign up to set email alerts
|

Content, cost, and context: A framework for understanding human signaling systems

Abstract: Humans frequently perform extravagant and seemingly costly behaviors, such as widely sharing hunted resources, erecting conspicuous monumental structures, and performing dramatic acts of religious devotion. Evolutionary anthropologists and archeologists have used signaling theory to explain the function of such displays, drawing inspiration from behavioral ecology, economics, and the social sciences. While signaling theory is broadly aimed at explaining honest communication, it has come to be strongly associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 95 publications
(196 reference statements)
1
38
0
Order By: Relevance
“…Many evolutionary scholars emphasize the costliness of prohibitions (Barker, Power, Heap, Puurtinen, & Sosis, 2019;Sosis, 2006), but our research indicates that other factors might influence prohibition. In line with the emphasis on costliness, we found that shamans are tabooed from sex and freely eating during healing ceremonies and initiations.…”
Section: Discussionmentioning
confidence: 68%
“…Many evolutionary scholars emphasize the costliness of prohibitions (Barker, Power, Heap, Puurtinen, & Sosis, 2019;Sosis, 2006), but our research indicates that other factors might influence prohibition. In line with the emphasis on costliness, we found that shamans are tabooed from sex and freely eating during healing ceremonies and initiations.…”
Section: Discussionmentioning
confidence: 68%
“…Second, men's investment in their children may serve as a signal to current and future mates and allies of their generosity, their sociability or their provisioning ability [36][37][38]. In the animal literature, Kokko et al [39] describe a similar concept, where males compete for females by demonstrating their prowess as good providers and there is a substantial literature more broadly positing that paternal care can serve as mating effort [40,41].…”
Section: (B) Paternity Confidence and Paternal Care Decisionsmentioning
confidence: 99%
“…Regarding human signaling, there is a variety of traits that cannot be directly observed and the only way to provide others with information about such strategic qualities is to signal them by the behavior directly linked to that trait (e.g., Barker et al, 2019 identify material, embodied and social capital as different kinds of qualities that are beneficial for humans to signal). For example, Bliege Bird and her colleagues (2001) have utilized CST to reconceptualize hunting and altruistic meat sharing among the Meriam turtle hunters.…”
Section: The Costly Signaling Theorymentioning
confidence: 99%